HEMOLYTIC DISEASE IN THE FETUS AND NEWBORNS - Dilfuza Narzikulovna Ibragimova; Zebo Jumaboevna Khusainova (Scholar Express Journals, 2022)
Hemolytic disease of the newborn is a congenital disease of the fetus and the newborn due to isoimmunological incompatibility of fetal and maternal blood for erythrocyte antigens. The disease remains one of the more frequent causes of jaundice and anemia in newborns. The incidence of GBN ranges from 3-6%. Lethality from this disease is currently 2.5%.
Keywords: Jaundice; Edema Syndrome; Fetal Dropsy; Liver